Proyecto «Pedro de Barcelos y la monarquía castellano-leonesa» - Maria do Rosário Ferreira (Atalaya)
This project intends to study, publish and highlight the last part of Pedro de Barcelos’ Cronica Geral de Espanha. Although there are two critical works (by Luis Felipe Lindley Cintra, published between 1951 and 1990 and by Diego Catalan and María Soledad de Andrés, 1970), the last part of this work has not yet been published. The project to publish this section began in April 2014 by a research team including Maria do Rosário Ferreira (manager), José Carlos Miranda, Filipe Alves Moreira and Maria Joana Gomes, all members of SMELPS (Medieval Seminar of Literature and Society). The project will last between 12 and 18 months.